2020
DOI: 10.3390/su12219172
|View full text |Cite
|
Sign up to set email alerts
|

Business Sustainability Strategy in a Cooperative Kibbutz Industry

Abstract: This article describes the management approach underlying the strategic business sustainability at a kibbutz factory situated in a non-privatized collective community. The business strategy explains the outstanding success of “T Industries”—which ranks as a leading kibbutz enterprise. The research utilized qualitative methods, using deep interviews combined with document analysis. The study found that the strategic management of T Industries comprises three major components: (1) socialist concern for community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
0
7
0
1
Order By: Relevance
“…The literature on the relationship between innovation strategies and business performance is extensive (see, e.g., [19][20][21]). However, for SMEs, several studies report mixed and/or inconclusive findings [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the relationship between innovation strategies and business performance is extensive (see, e.g., [19][20][21]). However, for SMEs, several studies report mixed and/or inconclusive findings [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on the relationship between innovation strategies and business performance is extensive (see, e.g., [19][20][21]). However, for SMEs, several studies report mixed and/or inconclusive findings [20,21]. On one hand, robust large-scale data surveys for SMEs as well as general, research in this area are scarce [22].…”
Section: Introductionmentioning
confidence: 99%
“…Además, es importante comunicar los avances y resultados de los esfuerzos de innovación y sostenibilidad, y establecer indicadores de desempeño sostenible para medir el impacto ambiental y social. Es importante también promover la Estrategia Empresarial [65]; [9]; [66]; [67]; [68]; [69]; [70]; [71]; [72].…”
Section: Recomendacionesunclassified
“…This reinforces a positive atmosphere and strengthens consensus, while avoiding conflict. The supportive work environment lowers the workers' level of stress and increases honesty [20,[27][28][29]. Employees have flexible schedules, permitting them to fulfill demands at work as well as deal with personal issues.…”
Section: Review Of the Literature 21 Social Interaction And Activity ...mentioning
confidence: 99%
“…Recent research in organizational sustainability indicated that a strong connection between economic behavior, managerial attitude, and business strategy affects workers' production [20,26,27]. Sustainability and healthy organizational culture depend on quality management of human resources.…”
Section: Cultural Sustainability and Managerial Attitudementioning
confidence: 99%